Junie eaudiobook A novel. - Eckstine, Erin Crosby (Books on Tape, 2025)
GOOD MORNING AMERICA BOOK CLUB PICK • A young girl must face a life-altering decision after awakening her sister’s ghost, navigating truths about love, friendship, and power as the Civil War looms. “An enrapturing tale of survival . . . Eckstine has poured a ton of heart into her characters.”— The Atlanta Journal-Constitution “The richly textured prose quickly pulled me into [Junie’s] treacherous yet magical world.”—Charmaine Wilkerson, New York Times bestselling author of Black Cake Sixteen years old and enslaved since she was born, Junie has spent her life on Bellereine Plantation in Alabama, cooking and cleaning alongside her family, and tending to the white master’s daughter, Violet. Her daydreams are filled with poetry and faraway worlds, while she spends her nights secretly roaming through the forest, consumed with grief over the sudden death of her older sister, Minnie. When wealthy guests arrive from New Orleans, hinting at marriage for Violet and upending Junie’s life, she commits a desperate act—one that rouses Minnie’s spirit from the grave, tethered to this world unless Junie can free her. She enlists the aid of Caleb, the guests’ coachman, and their friendship soon becomes something more. Yet as long-held truths begin to crumble, she realizes Bellereine is harboring dark and horrifying secrets that can no longer be ignored. With time ticking down, Junie begins to push against the harsh current that has controlled her entire life. As she grapples with an increasingly unfamiliar world in which she has little control, she is forced to ask herself: When we choose love and liberation, what must we leave behind?